Effects of anti-rheumatic herbal medicines on cellular adhesion molecules. Issue 6 (1st June 1999) - Chang, Deh-Ming; Kuo, San-Yuan; Lai, Jenn-Haung; Chang, Mu-Lan
Abstract : OBJECTIVE: To test the hypothesis whether herbal medicines ameliorate inflammatory diseases via the modulation of cellular adhesion molecules (CAMs). METHODS: Human neutrophils, synovial fibroblasts, and endothelial cells were incubated with different concentrations of Tripterygium Wilfordii Hook-f (TWH-f) or Tetrandrine in the presence or absence of interleukin 1 (IL1). The amount of soluble E-selectin, intercellular adhesion molecule-1 (ICAM-1) and vascular cellular adhesion molecule-1 (VCAM-1) secreted by cells were determined by ELISA. The cell surface expression of these three CAMs was detected by flow cytometry. RESULTS: TWH-f at high concentration (50 ng/ml) has a significant (p<0.05) inhibitory effect on both the secretion and the expression of the cellular adhesion molecules. However, Tetrandrine did not demonstrate the same effects. CONCLUSIONS: The cellular adhesion molecules of the endothelium and leucocytes may constitute excellent targets for the development of new anti-inflammation medicines. These results indicate that TWH could be a potential therapeutic agent in the treatment of inflammatory diseases.